P189 Ischemic Stroke: Through Adapted Clinical Guideline To Local Clinical Protocols. (15th August 2013) - Morozov, A; Stepanenko, A; Chagarna, N; Shylkina, O
Abstract : Background: The health care system of Ukraine required improvement in treatment of stroke patients based on evidence present in GIN. Objectives: To compare Ukrainian treatment practices with the best strategies for stroke management and to improve quality of health care on the basis of the identified differences. Methods: Multidisciplinary working group has prepared adapted guidelines "Modern principles of diagnosis and management of patients with acute ischemic stroke and TIA", "Recommendations for the management of patients with ischemic stroke and TIA", "Rehabilitation, prevention and management of complications and discharge planning in ischemic stroke" with regard of the evidence-based strategies for stroke treatment. Simultaneously, unified clinical protocols of medical care "Ischemic stroke" and "Systemic thrombolysis for stroke" were developed on the basis of the guidelines and then approved by the Ministry of Health of Ukraine in August 2012. Results: There were identified differences in the stroke treatment in Ukraine compared to the best practice, which resulted in amendments to the corresponding regulations in health care. In order to integrate these changes into clinical practice local protocols and critical pathways for management of stroke are developing in all healthcare facilities taking into account peculiarities of the region and available resources of the hospitals. Discussion: Local protocols comprise evidence-based statements which represent the best practice from clinical guidelines from GIN and other databases. Implications for Guideline Developers/Users: Measures enabling changes in existing medical practice are identified to ensure effective treatment of stroke patients within 4.5 hours after symptoms onset.